The suitability of fly ash based geopolymer cement for oil well cementing applications: A review - Dinesh, Kanesan; Sonny, Irawan; Syahrir, Ridha; Davannendran, Chandran *; Nuriman, A. A. (Asian Research Publishing Network (ARPN), 2018)
The increase in awareness towards global warming has prompted the research of alternatives to the conventional ordinary Portland Cement (OPC). In addition, studies have demonstrated that the use of geopolymer cement slurries resulted in lower carbon emission and superior cement properties compared to the ordinary Portland cement. In this study, the factors which affect the wellbore integrity in regards to cementing were identified and a comparison between Class G cement and Fly Ash Geopolymer (FAGP) cement pertaining to the identified factors were made. In addition, a thorough analysis on the factors affecting the properties of geopolymer in regards to its application in oil well cementing was performed. The results enable the finding of optimum parameters required to produce geopolymer cements for oil well applications. The FAGP cement achieved higher compressive strengths compared to Class G cement for all curing temperatures above 36⁰C. At optimum curing temperatures, for all curing time FAGP cement achieved higher compressive strengths in comparison Class G cement. Moreover, FAGP cement was found to be more susceptible to marine environment whereby curing medium of brine water resulted in higher compressive strengths. In addition, FAGP cement has lesser carbon footprint, superior chemical durability, lower permeability and higher crack propagation threshold in comparison the Class G cement. In addition, key variables which influence the compressive strength of FAGP cement such as type of activating solution, concentration of activating solution alkaline liquid to fly ash ratio, aging duration and water to binder ratio were identified and the corresponding optimum values in achieving highest compressive strength were suggested. The conclusion supports the usage of geopolymer cement for oil well cementing whereby it has an edge over conventional Portland cement for better short term and long term performance to ensure wellbore integrity throughout the producing life span of the well, with less hazards imposed on the environment.